(untitled) (Ustozlar uchun, 2025)
This article covers the topic “Implementation of AI in the Education of Senior Classes in Schools” and analyzes the implementation of artificial intelligence technologies in the teaching process in senior classes, its capabilities, advantages, problems and impact on educational effectiveness on a scientific basis. Today, AI tools - automated assessment systems, intelligent learning platforms, programs for creating personalized curricula, virtual laboratories, chatbot-teachers and analytical systems for monitoring student activity - are widely used in senior classes of secondary schools. Artificial intelligence plays an important role in teaching students based on an individual approach, creating exercises appropriate to their level of knowledge, optimizing the teaching process, developing students’ independent learning skills, and reducing the teacher’s methodological load. The article provides practical mechanisms for implementing AI technologies in the teaching process, changes in the roles of teachers and students, technical and psychological barriers, as well as recommendations for improving the quality of education. The results of the study show that artificial intelligence can significantly improve the effectiveness of education in higher education.